Analysis of the urban mobility of a medium-sized city in northern Rio Grande do Sul - Campestrini, Júlia Brum; Neckel, Alcindo; Silva, Thaísa Leal da (Revista Nacional de Gerenciamento de Cidades, 2022)
The lack of urban planning can cause several consequences for cities, especially in the face of accelerated population growth, resulting in obstacles to urban infrastructure and its services, especially in terms of mobility, making it necessary to think of strategies aimed at accessible development, and efficient and sustainable cities. In this context, the general objective of this study is to analyze the active mobility of the city of Passo Fundo/RS (Brazil), in particular, the bike paths and public transport in the city. Thus, initially, bibliographic research was carried out on the subject addressed, then data collection was carried out on the main points of public transport and cycle paths in the analyzed city. From the data collection, an analysis was carried out through maps and it was possible to perceive the importance of analyzing the urban mobility of the municipalities, which helps in the understanding of the current scenario, collaborating both in the management and in the municipal planning, as in the development of guidelines that adapt to the place in the search for a better quality of life for citizens.